Analisis Penerapan Akad Surat Berharga Syariah terhadap Penerbitan Sukuk Korporasi melalui Penawaran Umum pada Pasar Modal Syariah - Musnawati Musnawati (At-Tajdid : Journal of Islamic Studies, 2023)
The purpose of this study is to see and analyze the Sharia Securities Agreement on the issuance of Corporate Sukuk through a Public Offering in the Islamic Capital Market. The Sharia Securities Contracts used are the Mudharabah Contract, Ijarah Agreement and Wakalah Agreement for the issuance of Corporate Sukuk through Public Offerings. The research used Secondary data derived from the Company's Sukuk Development data from 2018 to August 2022 issued by the Share Capital Market Statistics of the Directorate of Sharia Capital Market, Financial Services Authority. The secondary data taken is in the form of information on Corporate Sukuk That Is Still Circulating based on the Mudharabah Contract, Ijarah Contract and Wakalah Contract. The data analysis method used is Multiple Linear Regression. The results showed that the number of Mudharabah Contracts issued had no effect on the issuance of Corporate Sukuk through Public Offerings, while Ijarah Contracts and Wakalah Contracts had an effect on the issuance of Corporate Sukuk through Public Offerings.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//